2016
DOI: 10.1186/s12909-016-0754-6
|View full text |Cite
|
Sign up to set email alerts
|

Private or salaried practice: how do young general practitioners make their career choice? A qualitative study

Abstract: Background: Young French postgraduates in general practice increasingly prefer salaried practice to private practice in spite of the financial incentives offered by the French government or local communities to encourage the latter. This study aimed to explore the determinants of choice between private or salaried practice among young general practitioners. Methods: A qualitative study was conducted in the South West of France. Semi-structured interviews of young general practitioners were audio-recorded until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Recently published studies showed that young physicians dismiss home visits [ 21 ]. Besides financial incentives, key factors that could enhance the physician’s willingness to participate in a home call include override of barriers like schedules and travel time, personal safety and liability, and further development of applications (diagnostic devices/tests, communication with doctors of other specialties) through technological advances that could increase the degree of certainty in working diagnosis [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies showed that young physicians dismiss home visits [ 21 ]. Besides financial incentives, key factors that could enhance the physician’s willingness to participate in a home call include override of barriers like schedules and travel time, personal safety and liability, and further development of applications (diagnostic devices/tests, communication with doctors of other specialties) through technological advances that could increase the degree of certainty in working diagnosis [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some GPs do not usually seek their peers for advice-alleging lack of time-they recognize that clinical discussions solved during clinical discussions [21]. Encouraging peer arrangements should be a key intervention [21,41,51], both within the specialty and with other specialists [29,41]. Group practice may also benefit the socials needs that physicians have.…”
Section: Protective Factorsmentioning
confidence: 99%
“…Even though national rural areas have difficulties in recruiting doctors, they had a significantly lower burnout prevalence. This may be related to the greater satisfaction given by their relationship with patients, clinical autonomy, and life in small communities [2,12,27,49,[51][52][53][54].…”
Section: Protective Factorsmentioning
confidence: 99%
“…In addition, work’s place and image in society are also changing, towards different ways of life and a better work–life balance. This phenomenon is also affecting highly dedicated professionals such as physicians [ 34 ]. Finally, the risks of engaging in these illness behaviours should probably be addressed during early medical training and then throughout careers, and on this last point, peer involvement and understanding would surely be valuable.…”
Section: Discussionmentioning
confidence: 99%